The first and last term of an A.P. are a and l respectively. If S is the sum of all the terms of the A.P. and the common difference is given by: l2 - a2 / k - (l+a). Then k = ? Please answer me fast.
Answers
![](https://hi-static.z-dn.net/files/d73/f6976f92c970e3f2ffb5d717df3dfac2.jpg)
k = 2S
Step-by-step explanation:
common difference is given by = (l² - a²) /(k - (l + a))
First Term = a
Last term = l
let say total terms = n
& Common difference = d
=> l = a + (n - 1)d
=> (n - 1) = (l - a)/d
=> n = (l - a)/d + 1
Sum of n terms
S = (n/2)(a + l)
=> n = 2S/(a + l)
2S/(a + l) = (l - a)/d + 1
=> 2S = (l² - a²)/d + a + l
=> (l² - a²)/d = 2S - a - l
=> d = (l² - a²) /(2S - a - l)
=> d = (l² - a²) /(2S - (a + l))
=> d = (l² - a²) /(2S - (l + a))
d = (l² - a²) /(k - (l + a)) given
Comparing
=> k = 2S
Learn more:
How to derive sum of n terms of an A.P? - Brainly.in
https://brainly.in/question/7849150
In an A.P if sum of its first n terms is 3n square +5n and it's Kth term ...
https://brainly.in/question/8236011
Find the sum of frist 51 terms of the AP whose 2nd term is 2 and 4th ...
https://brainly.in/question/7655866